Green bio-based PLA with waste tyre and graphene nanocomposites - Vinoth, Francisco; Mohd Bijarimi, Mat Piah (2020)
The aim of this study is to identify the optimum blend ratio by blending poly (lactic acid) (PLA) with waste tire crumb (WTR) with different composition in term of mechanical properties and identify the effect of different composition of graphene (GR) on the PLA/WTR in term of mechanical, thermal stability and morphology of nanocomposite. The sample was prepared by twin-screw extruder with a die of 25mm width and 0.5mm thickness. Results shows that incorporation of GR at 1.0PHR%, 2,0PHR% and 3.0PHR% improve the tensile properties od the PLA/WTR blend. Morphology as Scanning Electron Microscope (SEM) show that loading of GR in nanocomposites causes the pores decreases and from Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) show the thermal stability and thermal degradation of the blend improved when GR presence in the blend.